VALIDITAS DAN PRAKTIKALITAS LEMBAR KERJA PESERTA DIDIK (LKPD) BERMUATAN SOCIO SCIENTIFIC ISSUES PADA MATERI SISTEM IMUNITAS UNTUK FASE F SMA/MA - Fajrani, Suci; Fadilah, Muhyiatul (Jurnal Biogenerasi, 2025)
The study aims to produce LKPD containing socio-scientific issues on the immune system material that is valid and practical. This type of research is Research and Development. using the 4-D development research model. The subjects of this study were 40 students of Phase F class XII of SMA Negeri 1 Lubuk Basung. The data of this study are primary data obtained directly from the research subjects, namely two lecturers from the Biology Department, FMIPA UNP and a biology teacher at SMA Negeri 1 Lubuk Basung. Based on the research that has been done, the LKPD containing socio-scientific issues on the immune system material for phase F SMA/MA obtained an average validity value of 92.85% with very valid criteria by the validator. The LKPD developed has an average value of 94.89% with very practical criteria according to the teacher and has an average value of 89.32% with practical criteria according to students. Thus, it can be concluded that the LKPD developed is very valid and very practical.